The Potential of Rosella (Hibiscus sabdariffa L.) for Diabetes Mellitus Model Rats: Histopathological Focus on Pancreatic Organ - Putria, Sinta Julia Liona; Rohani, Siti; Suarni, Ertati; Astri, Yesi; Mundijo, Trisnawati (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Ethanolic extract of rosella flowers (Hibiscus sabdariffa L.) contains secondary metabolite compounds: flavonoids, alkaloids, saponins, and tannins. This study aims to determine whether the ethanol extract of rosella flowers has the potential to regenerate pancreatic β cells in white rats (Rattus norvegicus) with alloxan-induced diabetes mellitus models. Methods. The type of research used was an in vivo laboratory experimental study with a true experimental design. The experimental animals used as test objects in this study were male rats (Rattus norvegicus L.), weighing 100-110 grams. The test objects were 30 rats, divided into 6 groups randomly, each containing 5 rats, the groups consisted of K (N), K (-), K (+), P (1), P (2), and P (3). The level of histopathological damage to the pancreas was observed with HE staining at 400x magnification, using binocular light microscope type CX23 and BX51. Results. The study showed that the ethanol preparation of rosella flower extract at a dose of 1500 mg/kgBW and 3000 mg/kgBW BB was effective in regenerating pancreatic β cells with a damage value of 0 and at a dose of 750 mg/kgBW with a damage value of 2 did not provide a maximum regeneration effect on pancreatic β cells in male white rats induced by alloxan. Conclusion. The results of this research show that the ethanol extract of rosella flowers has an influence on the regeneration of pancreatic β cells so that it can be used for supportive treatment in the management of diabetes mellitus.